Second generation bioethanol production: A critical review - Aditiya H.B.; Mahlia T.M.I.; Chong W.T.; Nur H.; Sebayang A.H. (Elsevier Ltd, 2023)
Agricultural wastes; Agriculture; Air quality; Crude oil; Distillation; Ethanol; Feedstocks; Forestry; Fossil fuels; Petroleum deposits; Proven reserves; Bio-ethanol production; Critical review; Crude oil reserves; Fermentable sugars; Global temperatures; Lignocellulosic biomass; Second generation; Second generation bioethanol; Bioethanol